2019
DOI: 10.3889/oamjms.2019.707
|View full text |Cite
|
Sign up to set email alerts
|

Inter - Relationship of Awareness, Knowledge, Attitude, Some Socio-Economic Variables and Osteoporosis in Sample of Egyptian Women

Abstract: BACKGROUND:Osteoporosis is a global health problem, and its prevalence is rapidly increasing worldwide.AIM:The aim was to assess the awareness concerning some nutritional and socio-economic variables causes the disease in a sample of Egyptian women.METHODS:This study was done among 116 female volunteers. They were divided into two groups, pre and post-menopausal, with a mean age of 42.05 ± 8.25 & 51.13 ± 5.82 years and mean body mass index (BMI) of 30.83 ± 8.18 & 34.24 ± 8.80 kg/m2. A standardised questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Hage et al [31] found that women who have never heard of osteoporosis and had a lower level of education had lower knowledge scores. Other studies also found that the knowledge of osteoporosis in postmenopausal women diagnosed with the disease was limited [32][33][34], and level of education was a strong predictor of knowledge [34,35]. In China, Oumer et al [36] found that the awareness levels for osteoporosis were moderate; lower family income and education level were risk factors for lower awareness.…”
Section: Discussionmentioning
confidence: 98%
“…Hage et al [31] found that women who have never heard of osteoporosis and had a lower level of education had lower knowledge scores. Other studies also found that the knowledge of osteoporosis in postmenopausal women diagnosed with the disease was limited [32][33][34], and level of education was a strong predictor of knowledge [34,35]. In China, Oumer et al [36] found that the awareness levels for osteoporosis were moderate; lower family income and education level were risk factors for lower awareness.…”
Section: Discussionmentioning
confidence: 98%
“…They found out significant association in educational status and awareness for diet in chronic health conditions. 6,7 Patients should be aware that, legumes, potatos all pays important tole in each disease, as though some nutrients are provided with potatos as common dietary constitutent in many countries, major source of energy in potatos is starch which has high glycemic index. [8][9][10]…”
Section: Discussionmentioning
confidence: 99%
“…Public with a high level of awareness toward osteoporosis will apply Health Belief Model to motivate and seek further detail on health osteoporosis information and will learn more based on this theoretical framework.The finding of this study indicated that gender (p<0.038) and educational level (p<0.50) had a significant association with the level of knowledge regarding osteoporosis. Interestingly, a similar researcher byHassan et al (2019) in Egypt reported that a higher level of knowledge was found to be significant to women. In the United States of America,Wright et al (2019) surveyed that the educated group of samples had a significant association with the level of knowledge.…”
mentioning
confidence: 86%